2017
DOI: 10.3389/fmicb.2017.01797
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Click Beetle Luciferase Reporter System for Enhanced Bioluminescence Imaging of Listeria monocytogenes: Analysis in Cell Culture and Murine Infection Models

Abstract: Listeria monocytogenes is a Gram-positive facultative intracellular pathogen that is widely used as a model organism for the analysis of infection biology. In this context, there is a current need to develop improved reporters for enhanced bioluminescence imaging (BLI) of the pathogen in infection models. We have developed a click beetle red luciferase (CBR-luc) based vector (pPL2CBRopt) expressing codon optimized CBR-luc under the control of a highly expressed Listerial promoter (PHELP) for L. monocytogenes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
(71 reference statements)
0
20
0
Order By: Relevance
“…See also Figure S4. (legend continued on next page) Smith et al, 2017;Stromnes et al, 2015;Ur Rahman et al, 2017). CB induces priming, intratumoral accumulation, and rapid intratumoral dysfunction of CB-specific T cells in PDA.…”
Section: Discussionmentioning
confidence: 99%
“…See also Figure S4. (legend continued on next page) Smith et al, 2017;Stromnes et al, 2015;Ur Rahman et al, 2017). CB induces priming, intratumoral accumulation, and rapid intratumoral dysfunction of CB-specific T cells in PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies had demonstrated that Fluc, Luc2, and CBR had higher sensitivity than PpyRE9h to report promoter activity in other systems. 21, 22 Hence, these red luciferases were assayed in Giardia .…”
Section: Resultsmentioning
confidence: 99%
“…Animals received substrates and bacteria by gastric inoculation before imaging, furimazine (1/20 dilution of Nano-Glo® Luciferase substrate, 200 mL gavage volume, Promega) is the substrate for NLuc system and D-luciferin (150 mg kg À1 , PerkinElmer) is for FLuc and CBRLuc systems. 35,36 Bioluminescence images were acquired at room temperature on a Berthold NightOWL LB 983 Imaging System (Berthold Technologies, Bad Wildbad, Germany). The images were acquired with open lter and exposure time ranges from 1 to 3 min according to the signal intensity, the luminescence counts acquired under different exposure time were all normalized as the average value (total counts/ exposure time) to ensure the reasonable comparison, and the pseudo colour images represented the light intensity (from red for most intense to blue for least intense).…”
Section: Whole Body Imaging Acquisitionmentioning
confidence: 99%
“…S1 ‡), which was consistent with previously-reported results. 36 The short wavelength of luciferase system may limit its application in vivo, due to the weak ability to penetrate host tissues compared with long emission systems. 37 The emission maximum of NLuc was 460 nm, which was shorter than FLuc (560 nm) and CBRLuc (613 nm).…”
Section: In Vitro Bioluminescence Properties Of Recombinant Bacteriamentioning
confidence: 99%